Political Changes in Croatia and the Croatian Emigrant Press in Chile - Marina Perić (Migracijske i etničke teme, 2005)
The paper gives an overview of the Croatian emigrant press in Chile through five historical periods (before World War I, during World War I, between the two world wars, during World War II, after World War II). Parallels are drawn between political changes in Croatia and changes in the contents and themes of the emigrant press. One emigrant newspaper is analysed for each historical period, via the content analysis method, and front-page articles are taken as the units of analysis. Apart from the messages’ contents, their form is analysed, so as to assess opinions that the messages’ senders transmit to their receivers. Based on the analysis of the newspapers, the author concludes that changes in Croatia had an important influence on the emigrant press, which was especially visible in the period during World War I and World War II. In the period from World War I onwards, headings and themes in the emigrant press were used to propagate Yugoslavism and a sense of belonging to the Yugoslav nation and state. The identity of the emigrants changed under the influence of political changes in Croatia. Up to World War I they were mainly anti-Austrian oriented, and in the next four periods they accepted the state and the government of both the first and the second Yugoslavia, identifying themselves with Yugoslavia, and raising their descendents in a Yugoslav spirit.